(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Terrorism and its means have been applied since Ancient times, and over the years the human development and technologies have transformed it into a serious threat to the civilians, societies, countries and even to the international security. The globalisation of terrorism demands new approaches for the effective counteraction, in accordance to the dynamically changing security environment of the 21st century. Meanwhile, with the escalation of the conflict between Hamas and Israel, the issue about the terrorism threat took the headlines, both in the information space and at the highest political level. The discussion focuses on the specific methods of combating terrorism and the permissible level of violence that should be applied in this fight. This paper seeks to answer important questions regarding security by presenting an analysis of some basics concerning the phenomenon of "terrorism". For this purpose, the applied methods of the research include careful examination of terrorism’s evolution throughout history, the factors that have influence over terrorists’ attitude, the motivation which fuels one’s decision to become a part of a terrorist group and its most striking recent manifestation. Furthermore, the paper puts the emphasis on the necessity of developing new counter-terrorism strategies along with incorporation of the newest technologies in the security sector.